2020
DOI: 10.1002/open.201900324
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Phase Quasi‐Epitaxial Growth of Highly Stable, Monolithic UiO‐66‐NH2 MOF thin Films on Solid Substrates

Abstract: High quality, monolithic UiO-66-NH 2 thin films on diverse solid substrates have been prepared via a low temperature liquid phase epitaxy method. The achievement of continuous films with low defect densities and great stability against high temperatures and hot water is proven, clearly outperforming other reported types of MOF thin films.Metal-organic frameworks (MOFs) or porous coordination polymers (PCPs) represent a class of highly functional solid materials assembled from metal or metal/oxo nodes and di-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Furthermore, Pan et al [ 42 ] explored a pure aqueous synthesis route for ZIF-8 and reported excelling stability of the material in boiling water and methanol. Considering ZIF-8 SURMOFs like the ones explored in this work, a previous work [ 16 ] showed that the films lost their crystallinity after being immersed in boiling water for 1 h and SEM images revealed a complete detachment of the film from the substrate. Moreover, Sheng et al [ 44 ] explored the effect of varying Zn salts on the hydrothermal stability of ZIF-8 and observed significant degradation in the material after 10 days with the exception of the ZIF-8 derived from Zn acetate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Pan et al [ 42 ] explored a pure aqueous synthesis route for ZIF-8 and reported excelling stability of the material in boiling water and methanol. Considering ZIF-8 SURMOFs like the ones explored in this work, a previous work [ 16 ] showed that the films lost their crystallinity after being immersed in boiling water for 1 h and SEM images revealed a complete detachment of the film from the substrate. Moreover, Sheng et al [ 44 ] explored the effect of varying Zn salts on the hydrothermal stability of ZIF-8 and observed significant degradation in the material after 10 days with the exception of the ZIF-8 derived from Zn acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al [ 49 ] reported also high stability of the material in water and in fluoride-containing solution. Continuing with water scenarios, a previous work explored the stability of UiO-66-NH 2 SURMOF films in boiling water [ 16 ]. The results showed that for these MOF thin films the crystallinity and the adhesion to the substrate was unchanged after immersion for one hour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 37 ] Over the last two decades, Wöll and colleagues have implemented the LPE technique for building SURMOFs for many applications, employing conventional MOFs such as ZIFs, IRMOF‐n, MIL‐n or HKUST‐1, and recently UiO‐NH 2 ‐66. [ 27,44,45 ] Briefly, a pretreated quartz or silicon substrate was placed in a reactor at 55 °C (which is 10 °C lower than in our previous report). [ 37 ] Thereafter, the substrate was immersed in ethanolic solution of either Ln(NO 3 ) 3 or H 3 BTC alternatingly.…”
Section: Figurementioning
confidence: 99%